2021
DOI: 10.1111/jpi.12769
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from melatonin‐preconditioned mesenchymal stem cells containing USP29 repair traumatic spinal cord injury by stabilizing NRF2

Abstract: Spinal cord injury (SCI) is a devastating trauma that leads to irreversible motor and sensory dysfunction and is, so far, without effective treatment. Recently, however, nano-sized extracellular vesicles derived from preconditioned mesenchymal stem cells (MSCs) have shown great promise in treating various diseases, including SCI. In this study, we investigated whether extracellular vesicles (MEVs) derived from MSCs pretreated with melatonin (MT), which is well recognized to be useful in treating diseases, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 78 publications
(85 reference statements)
4
49
0
1
Order By: Relevance
“…The findings concerning microglia are, again, in good agreement with corresponding actions of directly administered melatonin [59]. The microvesicles collected from melatonin-pretreated cells were also shown to be enriched with USP29 (ubiquitin-specific protease 29, systematic name: ubiquitin carboxyl-terminal hydrolase 29) [227], a deubiquitinase that prevents the proteasomal decay of Nrf2 (nuclear factor erythroid 2-related factor 2), a key transcription factor of anti-inflammatory and antioxidant signaling. This study also revealed another novel aspect of MSC function concerning the stability of Usp29 mRNA, which was enhanced by melatonin, but strongly decreased by overexpression of METTL3 (methyltransferase-like 3), an RNA methylating enzyme, also referred to as the "writer" of adenosine 6-methylation.…”
Section: Msc-derived Exosomes With Protective Anti-inflammatory and A...supporting
confidence: 73%
See 2 more Smart Citations
“…The findings concerning microglia are, again, in good agreement with corresponding actions of directly administered melatonin [59]. The microvesicles collected from melatonin-pretreated cells were also shown to be enriched with USP29 (ubiquitin-specific protease 29, systematic name: ubiquitin carboxyl-terminal hydrolase 29) [227], a deubiquitinase that prevents the proteasomal decay of Nrf2 (nuclear factor erythroid 2-related factor 2), a key transcription factor of anti-inflammatory and antioxidant signaling. This study also revealed another novel aspect of MSC function concerning the stability of Usp29 mRNA, which was enhanced by melatonin, but strongly decreased by overexpression of METTL3 (methyltransferase-like 3), an RNA methylating enzyme, also referred to as the "writer" of adenosine 6-methylation.…”
Section: Msc-derived Exosomes With Protective Anti-inflammatory and A...supporting
confidence: 73%
“…This is explained by the PTEN-catalyzed dephosphorylation of PIP3 (phosphatidylinositol 3,4,5-tris-phosphate) to PIP2, a known inhibitor of Akt signaling. In a study on spinal cord injury, the melatoninpromoted M1-to-M2 shift was corroborated for both macrophages and microglia when treated with microvesicles from melatonin-preconditioned MSCs [227]. The findings concerning microglia are, again, in good agreement with corresponding actions of directly administered melatonin [59].…”
Section: Msc-derived Exosomes With Protective Anti-inflammatory and A...mentioning
confidence: 52%
See 1 more Smart Citation
“…During the process of skin and muscle wounds healing, macrophages will shift from M1 to M2 phenotype in response to the change of microenvironmental stimulus signals at the lesion site (50,51). Whereas, an analogous M1 to M2 conversion was not observed in the process of spinal cord tissue repair, and the persistent presence of M1 macrophages would exacerbate secondary injury (52)(53)(54). Therefore, inducing macrophages switch towards M2 phenotype following acute inflammatory response may contribute to anatomical and functional recovery post-SCI.…”
Section: Inflammatory Response After Scimentioning
confidence: 99%
“…Melatonin‐stimulated extracellular vesicles (MEVs) upregulated ubiquitin‐specific protease 29 (USP29) to deubiquitinate and stabilize NRF2, thereby regulating microglia/macrophages polarization and mitochondrial function. ( 44 )…”
Section: Discussionmentioning
confidence: 99%